The Efficacy Of Insect Growth Regulators On Tropical Bed Bugs, Cimex Hemipterus (Fabricus) And Its Microbial Fauna Using Pcr Based Culture Dependent And 16S Rrna - Taibukahn, Nurhidayah (2024)
Bed bugs are ectoparasites that primarily feed on humans and secondarily on other warm-blooded organisms. Two widespread species with medical relevance are the common bed bugs, Cimex lectularius L. and the tropical bed bugs, Cimex hemipterus (F.). Novel insecticides formulation are highly demanded due to the difficulties in battling bed bugs. For total eradication, it is important to administer long-term treatment using chemical and non-chemical active ingredients since bed bugs are capable in modulating their resistance mechanisms. This research exploits the regulation of microbial endosymbiont between insecticides treated and untreated tropical bed bugs, Cimex hemipterus employing PCR based culture dependent and 16S rRNA metagenomic based culture independent analysis. Prior to this study, field strain fifth stage nymph and adult bed bugs collected from residential area around Penang Island were treated with five classes of insecticides comprised of manufactured brand chlorfluazuron, chlorfluazuron, pyriproxyfen, methoprene, tebufenozide and β-cyfluthrin + imidacloprid act as positive control. The treated insecticide poses different mode of action in which chitin synthesis inhibitor, juvenile hormone analogue, ecdysteroid receptor agonist and mixture of pyrethroid and neonicotinoids that were applied at four different concentrations (100, 500, 1000 and 10 000ppm). Among the insecticides classes, manufactured brand chlorfluazuron and β-cyfluthrin + imidacloprid demonstrated the prominent mortality performance within the two weeks xviii of surface contact bioassay compared to other insecticides which offers less than 50% of mortality percentage.